2001
DOI: 10.1523/jneurosci.21-17-06933.2001
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptor Sensitization by Extracellular Signal-Regulated Kinases

Abstract: Inflammatory pain, characterized by a decrease in mechanical nociceptive threshold (hyperalgesia), arises through actions of inflammatory mediators, many of which sensitize primary afferent nociceptors via G-protein-coupled receptors. Two signaling pathways, one involving protein kinase A (PKA) and one involving the epsilon isozyme of protein kinase C (PKCepsilon), have been implicated in primary afferent nociceptor sensitization. Here we describe a third, independent pathway that involves activation of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(90 citation statements)
references
References 51 publications
3
87
0
Order By: Relevance
“…In the central nervous system, β 2 ARs are located on thalamic, cerebellar (Rainbow et al, 1984, Nicholas et al, 1996), and spinal dorsal horn neurons (Nicholson et al, 2005) as well as glial cells (Stone and Ariano, 1989, Salm and McCarthy, 1992). The contribution of β 2 ARs to enhanced pain sensitivity is in line with results from previous studies demonstrating that epinephrine activates β 2 ARs located on primary afferent nociceptors and produces a hyperalgesic state in rats (Khasar et al, 1999a, Khasar et al, 1999b, Aley et al, 2001, Khasar et al, 2003). Additionally, common variants of the human β 2 AR gene, coding for differences in receptor expression and internalization, are associated with the onset of TMD (Diatchenko et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…In the central nervous system, β 2 ARs are located on thalamic, cerebellar (Rainbow et al, 1984, Nicholas et al, 1996), and spinal dorsal horn neurons (Nicholson et al, 2005) as well as glial cells (Stone and Ariano, 1989, Salm and McCarthy, 1992). The contribution of β 2 ARs to enhanced pain sensitivity is in line with results from previous studies demonstrating that epinephrine activates β 2 ARs located on primary afferent nociceptors and produces a hyperalgesic state in rats (Khasar et al, 1999a, Khasar et al, 1999b, Aley et al, 2001, Khasar et al, 2003). Additionally, common variants of the human β 2 AR gene, coding for differences in receptor expression and internalization, are associated with the onset of TMD (Diatchenko et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…ERK1/2 activation in primary afferents has been suggested to be involved in peripheral sensitisation in acute pain conditions 25 26 27. We therefore examined the p-ERK1/2 labelling 2 min after mechanical stimulation (fig 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory mediators, such as prostaglandin E 2 , serotonin, epinephrine, and nerve growth factor (NGF), produce hyperalgesia through activation of protein kinase A (PKA) or protein kinase C (PKC) in primary afferent neurons (Gold et al, 1998;Khasar et al, 1999). Recently, it has been shown that the ERK cascade acts in epinephrine-induced hyperalgesia; also, the Ras-MEK-ERK pathway is activated independently of PKA or PKC (Aley et al, 2001;Dina et al, 2003). Furthermore, NGF injected into the peripheral tissue increases p-ERK labeling in tyrosine kinase A (trkA)-containing DRG neurons (Averill et al, 2001;Delcroix et al, 2003).…”
Section: Erk Activation In Drg Neurons After Noxious Stimulationmentioning
confidence: 99%